Some Properties of Relative Bi-(Int-)Γ-Hyperideals in Ordered Γ-Semihypergroups - Rao, Yongsheng; Xu, Peng; Shao, Zehui; Kosari, Saeed; Omidi, Saber (Frontiers in Physics, 2020)
In this article, we study the concept of relative bi-Γ-hyperideals (J-bi-Γ-hyperideals) in ordered Γ-semihypergroups and present some related examples of this concept. Especially, characterization of J-simple ordered Γ-semihypergroups in terms of J-bi-Γ-hyperideals is given. Furthermore, we define the notion of J-(bi-)int-Γ-hyperideals in ordered Γ-semihypergroups and investigate its related properties. We show that J-int-Γ-hyperideals and J-Γ-hyperideals coincide in a J-regular ordered Γ-semihypergroup.